Family Planning Policies in Peru (1995-2023): Ontological Problems on Fertility and Infertility in Andean and Amazonian Culture - Apaza-Ticona, Jorge; Gallardo-Lorenzo, Ignacio; Mamani-Flores, Adderly; Inquilla-Mamani, Juan; Alanoca-Arocutipa, Vicente; Calderón-Torres, Alfredo (Journal of Ecohumanism, 2024)
The research proposes a historical analysis of family planning policies in force from 1995 to 2023, with the objective of understanding the problems derived from the Voluntary Surgical Contraception (VSC) program implemented between 1995 and 2000, as well as the current decline of the health system in relation to sexual health and family planning. It addresses the influence of conservative-oriented governments and policies, as well as the interaction with Andean, Amazonian and urban cultural conceptions of fertility and infertility. The methodology employed is historical in nature, with an anthropological and qualitative approach. The findings highlight that policies related to sexuality and family planning in the historical context of the country did not take into account the cultural values and perspectives of local communities, which has contributed to a social gap in the field of public health. It is evident that the mass sterilization policies implemented in Peru during the 1990s suffered from lack of informed consent, pressure and coercion on individuals, having a disproportionate impact on the most vulnerable communities. Therefore, this study seeks to provide guidance and recommendations to address the current problem identified.